Quality of Labor Epidural Analgesia at a High-volume Tertiary Care Obstetric Unit: A Before-and-After Study. Issue 4 (22nd December 2021) - Easther, R.G.; Downey, K.; Watts, N.; Ye, X.Y.; Carvalho, J.C.A.
Abstract : ( Reg Anesth Pain Med . 2021;46:157–163. doi: 10.1136/rapm-2020-101873. [Epub November 6, 2020]. PMID: 33159006) Randomized controlled trials show neuraxial analgesia minimizes pain and improves patient experience across North America, yet these findings are under controlled conditions within homogenous populations. Also, practice changes were made between 2011 and 2017 at the institution's obstetric unit including a more consistent epidural loading dose of local anesthetic plus fentanyl, increased hourly and maximum limits of bupivacaine, and conversion from continuous epidural infusion to programmed intermittent epidural bolus (PIEB) regimen. Any changes in reported data between the 2 time periods provide insight on the quality of labor analgesia. This study aimed to improve maternal care and outcomes by further understanding the safety, quality, and patient satisfaction of labor analgesia using prospective observational studies.